2016
DOI: 10.1111/jnc.13454
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic investigation of sildenafil using positron emission tomography and determination of its effect on cerebrospinal fluid cGMP levels

Abstract: Sildenafil (Viagra) is a selective inhibitor of phosphodiesterase type 5 (PDE5), which degrades cyclic guanosine monophosphate to the linear nucleotide. Sildenafil is acutely used in erectile dysfunction and chronically in pulmonary hypertension. Evidence in the last decade shows that sildenafil may have potential as a therapeutic option for Alzheimer's disease or other neurodegenerative disorders. The purpose of this work was to explore whether sildenafil crosses the blood-brain barrier. Pharmacokinetic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…In animal studies sildenafil is reported to pass the blood-brain barrier [51], though similar is not clearly evident in humans [52]. Muscle biopsies from the patients showed reduced nNOS protein expression and a corresponding reduction in PDE5 expression [23], which could cause the patients to be less sensitive to PDE5 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies sildenafil is reported to pass the blood-brain barrier [51], though similar is not clearly evident in humans [52]. Muscle biopsies from the patients showed reduced nNOS protein expression and a corresponding reduction in PDE5 expression [23], which could cause the patients to be less sensitive to PDE5 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic effect should lead to achieve a degree of histone 3 acetylation that is not possible with HDAC6-selective inhibitors (eg, Ricolinostat) and, on the other hand, these new molecules will also achieve a degree of tubulin acetylation that has been impossible to obtain with the FDA-approved class I inhibitor, valproic acid (Gurvich et al, 2004). Moreover, the compounds proposed will have better brain permeability than the FDA-approved HDAC (Kazantsev and Thompson, 2008) and PDE5 inhibitors (eg, Sildenafil and Tadalafil, with a logBBo0) (Garcia-Barroso et al, 2013;Gomez-Vallejo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Gómez‐Vallejo et al . () cite several studies showing neuroprotective effects of PDE5 inhibition in brain injury and neurotoxicity models. Furthermore, PDE5 inhibition moderates cognitive decline in mouse models of Alzheimer′s disease.…”
mentioning
confidence: 99%
“…This latter, procognitive, aspect of PDE5 is the motivation for the PET study by Gómez‐Vallejo et al . (), who proved a central action of sildenafil through increases in the cGMP content of cerebrospinal fluid from non‐human primates, measured using a very sensitive assay. However, their rat PET studies showed rather low cerebral uptake of [ 11 C]sildenafil (< 0.1% ID/g), and no evidence for displaceable binding in brain parenchyma (as distinct from the cerebrovascular lumen, which had some specific binding).…”
mentioning
confidence: 99%
See 1 more Smart Citation